A composite clarifying agent, its preparation method and application
Patent Information
- Application Number
- CN202611063149.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-17
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2046-07-17
AI Technical Summary
按照目前的芒硝+焦锑酸钠组合澄清,因其反应温度及反应时间的特性,其澄清的效果也不断变差
(1)本发明将多种硫酸盐复合形成极高的构型熵,有效地提高了澄清剂的分解点,可以提升至1100℃以上,复合澄清剂多元固溶提升相稳定域,还延迟分解释放气体;
Smart Images

Figure CN122562324B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of photovoltaics, and relates to photovoltaic glass clarifying agents, and more particularly to a composite clarifying agent, its preparation method and application. Background Technology
[0002] With the increasing demand for high light transmittance in photovoltaic glass, reducing the iron content in the glass has become a core issue affecting the quality of photovoltaic modules. Reducing iron ions decreases the absorption of sunlight, thereby increasing light transmittance and directly improving the power generation efficiency of photovoltaic modules. Currently, mainstream photovoltaic glass manufacturers have controlled the iron content to below 100 ppm.
[0003] The clarification process of molten glass is a crucial step in glass melting, directly impacting the quality of the raw glass sheet. The clarification process aims to establish an equilibrium between the gases in the bubbles, the gases within the furnace, and the gases physically dissolved and chemically combined in the molten glass. This allows visible bubbles to float to the surface of the molten glass and be expelled, while smaller bubbles shrink and disappear during cooling. Lower iron content in photovoltaic glass leads to higher light transmittance, but also increases the difficulty of clarification and bubble removal. During glass melting, low iron content results in weak convection in the molten glass, hindering bubble removal and necessitating higher clarification temperatures and longer residence times, thus increasing energy consumption and costs. Therefore, it is necessary to introduce highly efficient clarifying agents that rely on high-temperature oxygen release from variable-valence oxides to enhance clarification.
[0004] Currently, the mainstream clarifying agents in the photovoltaic glass industry are sodium sulfate plus antimony-based clarifying agents (sodium antimonate pyroantimonate or antimony trioxide), which account for over 90% of production lines. However, as the daily melting capacity of photovoltaic glass furnaces continues to increase, the furnace size is also increasing. Furnaces with a daily melting capacity of 1200 tons / day have become the mainstream, and furnaces with a daily melting capacity of 1600 tons / day are constantly increasing. The number of small melting furnaces is also gradually increasing to ten pairs of small furnaces. The clarifying zone of the furnace is also constantly shifting further back, and the melting hot spot temperature is constantly increasing to match the needs of large-size furnaces. With the current combination of sodium sulfate and sodium antimonate pyroantimonate for clarification, due to the characteristics of its reaction temperature and reaction time, its clarification effect is continuously deteriorating.
[0005] Therefore, it is necessary to research new composite clarifying agents to meet the clarification requirements of photovoltaic glass in large kilns. Summary of the Invention
[0006] In view of the shortcomings of the existing technology, the purpose of this invention is to provide a composite clarifying agent, its preparation method and application. By combining multiple sulfates, multiple elements are intercalated to form a stable crystal lattice structure, which has a higher decomposition temperature and can delay and control the release of gas, thus achieving the effect of high-temperature clarification.
[0007] To achieve this objective, the present invention adopts the following technical solution: In a first aspect, the present invention provides a composite clarifying agent, the general formula of which is A2B2(SO4)3; wherein A includes Na and K, and B includes Mg, Ca, Sr, Ba and Zn.
[0008] This invention synthesizes multiple sulfates to obtain a stable crystal structure. The high-entropy design at the A-site can adjust the lattice size and introduce micro-strain, while the high-entropy design at the B-site can generate lattice distortion to hinder dislocation movement and atomic diffusion, thereby improving the overall thermal stability of the crystal and effectively increasing the decomposition point of the clarifying agent. This invention mixes Na (with a small ionic radius) with K (with a large ionic radius) to optimize lattice energy and ion mobility. By adjusting the sodium-potassium ratio, the ordered nature of a single alkali metal is broken, increasing the degree of disorder. In this invention, Zn can achieve high-entropy modification at the B-site, promoting lattice distortion. The moderate zinc ion radius further enhances the stability after lattice distortion.
[0009] As a preferred embodiment of the present invention, the general formula of the composite clarifying agent is: (Na x1 K x2 )2(Mg y1 Ca y2 Sr y3 Ba y4 Zn y5 )2(SO4)3; where x1+x2=1, y1+y2+y3+y4+y5=1.
[0010] This invention highly mixes multiple elements to form an extremely high configurational entropy, which stabilizes the crystal structure and greatly increases the decomposition point. Furthermore, the intercalation of elements with different atomic sizes leads to severe lattice distortion, further improving stability. In addition, the lattice distortion and complex chemical environment make atomic migration exceptionally difficult, widening the thermal reaction range and achieving a delayed diffusion effect.
[0011] As a preferred embodiment of the present invention, x1 satisfies: 0.4≤x1≤0.6.
[0012] In a preferred embodiment of the present invention, y1 satisfies: 0.1 ≤ y1 ≤ 0.4; The condition y2 satisfies: 0.1 ≤ y2 ≤ 0.4; The condition y3 satisfies: 0.1 ≤ y3 ≤ 0.3; The condition y4 satisfies: 0.1 ≤ y4 ≤ 0.3; The condition y5 satisfies: 0.1≤y5≤0.2.
[0013] This invention controls the content of each element within the above-mentioned range, which not only increases the decomposition temperature of the composite clarifying agent, but also broadens the thermal reaction range, thereby improving the clarification effect.
[0014] In a second aspect, the present invention provides a method for preparing the composite clarifying agent described in the first aspect. The preparation method includes: mixing at least seven sulfates, adding a dispersing solvent and stirring evenly, and grinding to obtain a mixture, followed by pre-reaction, phase formation treatment and densification treatment in sequence to obtain the composite clarifying agent.
[0015] This invention employs a pre-reaction process to remove ionized water and water of crystallization from sulfates, achieves lattice distortion through phase formation treatment, and utilizes densification treatment to broaden the thermal reaction range of the composite clarifying agent.
[0016] As a preferred embodiment of the present invention, the at least seven sulfates include at least two first sulfates and five second sulfates; The two primary sulfates include sodium sulfate and potassium sulfate; The five secondary sulfates include at least magnesium sulfate, calcium sulfate, strontium sulfate, barium sulfate, and zinc sulfate.
[0017] The first sulfate added in this invention adjusts the lattice size and introduces micro-strain, which can optimize lattice energy and ion mobility. At the same time, the second sulfate can produce huge lattice distortion, thereby greatly improving the overall thermal stability of the crystal.
[0018] In one embodiment of the present invention, the dispersion medium used in the mixing process includes water and alcohols, wherein the alcohols include at least one of methanol, ethanol or propanol; The dispersant used in the mixing process includes at least one of ammonium polyacrylate, sodium polyacrylate, and polyacrylic acid.
[0019] In one embodiment of the present invention, the grinding process is performed at a speed of 300-800 rpm for 1-4 hours.
[0020] This invention controls the grinding speed within the above-mentioned range to avoid excessive local temperature and oxidation decomposition caused by excessively high speed, while preventing uneven mixing and substandard particle size caused by excessively slow speed.
[0021] As a preferred embodiment of the present invention, the pre-reaction includes a first drying process, a second drying process, and a first cooling process performed sequentially.
[0022] In this invention, the primary drying process can remove the deionized water in the sulfate, and the secondary drying process is used to further remove the water of crystallization in the sulfate.
[0023] In one embodiment of the present invention, the temperature of the primary drying process is 110~120℃ and the time is 10~15h.
[0024] In one embodiment of the present invention, the temperature of the secondary drying process is 430~470℃ and the time is 2~5h.
[0025] In one embodiment of the present invention, the primary cooling includes: cooling the furnace to room temperature.
[0026] As one embodiment of the present invention, the phase formation process includes: sequentially subjecting the pre-reaction mixture to a first heating, a second heating, and a second cooling.
[0027] This invention achieves lattice distortion and improves the thermal stability of the clarifying agent through a segmented heating process.
[0028] In one embodiment of the present invention, the temperature after the first heating is 700~800℃, and the holding time is 1~3h.
[0029] In one embodiment of the present invention, the temperature after the second heating is 800~850℃, and the holding time is 2~4h.
[0030] In one embodiment of the present invention, the secondary cooling includes: cooling the furnace to room temperature.
[0031] As a preferred embodiment of the present invention, the densification process includes: pulverizing the mixture after the phase formation treatment to obtain a powder mixture; then mixing the powder mixture with a binder and granulating it to obtain a dense material; and subjecting the dense material to sintering and cooling three times in sequence to obtain the composite clarifying agent.
[0032] In one embodiment of the present invention, the average particle size of the powder mixture is <200 mesh.
[0033] In one embodiment of the present invention, the diameter of the dense material is 0.5~2mm.
[0034] This invention shapes dense materials into spherical shapes and controls their diameter within the aforementioned range to ensure that the gas produced by the reaction diffuses slowly from the inside, preventing the gas from escaping rapidly from the surface of the loose powder and causing an excessively fast reaction.
[0035] In one embodiment of the present invention, the sintering treatment is performed at a temperature of 900~950℃ for a time of 1.5~3h. In one embodiment of the present invention, the three-stage cooling process includes: cooling the furnace to room temperature and then storing it in a desiccator.
[0036] Thirdly, the present invention provides an application of the composite clarifying agent described in the first aspect, wherein the composite clarifying agent is used for clarifying photovoltaic glass.
[0037] The composite clarifying agent of this invention has no side effects on photovoltaic glass, can be applied in batches and mass-produced, and also reduces raw material costs.
[0038] Compared with the prior art, the beneficial effects of the present invention are as follows: (1) The present invention combines multiple sulfates to form an extremely high configuration entropy, which effectively increases the decomposition point of the clarifying agent to above 1100℃. The composite clarifying agent improves the stability domain of the phase by multi-component solid solution and delays the decomposition and release of gas. (2) In the composite clarifying agent of the present invention, elements of different atomic sizes are intercalated to each other, which hinders dislocation movement and atomic diffusion, and greatly improves the overall thermal stability of the crystal. (3) By designing the proportion of each component in the composite clarifying agent, the present invention has a wider thermal reaction range, which can react multiple times during the melting process, delay the release of gas for clarification, and thus match the clarification needs of large-size photovoltaic glass furnaces. (4) The composite clarifying agent of the present invention has no side effects on photovoltaic glass and can be applied in batches and produced on a large scale. Compared with traditional clarifying agents, it can further reduce the amount of sodium pyroantimonate and reduce raw material costs. Attached Figure Description
[0039] Figure 1 The image shows the XRD test results of the main phase of the composite clarifying agent in Comparative Example 1.
[0040] Figure 2 The image shows the XRD test results of the main phase of the composite clarifying agent in Example 2.
[0041] Figure 3 The graph shows the DSC-TGA test results of the composite clarifying agents of Examples 1-4 and Comparative Example 1.
[0042] Figure 4 This is a high-temperature visual image of the composite clarifying agent in Example 2.
[0043] Figure 5 This is a high-temperature visual image of the Glauber's salt clarifying agent in Comparative Example 9. Detailed Implementation
[0044] It should be understood that the scope of this invention can be defined by lower and upper limits. The selected lower and upper limits define the boundaries of a specific range. The range defined in this way can be defined by the inclusion or exclusion of endpoints. Any endpoint can be independently selected for inclusion or exclusion, and all lower and upper limits can be arbitrarily combined to form new ranges. That is, any lower limit can be combined with any upper limit to form an effective range. For example, if the ranges of 60~120 and 80~110 are listed for specific parameters, it should be understood that the ranges of 60~110 and 80~120 also fall within the scope of this invention. In addition, if the minimum range values 1 and 2 are listed, and the maximum range values 3, 4 and 5 are also listed, then all ranges of 1~3, 1~4, 1~5, 2~3, 2~4 and 2~5 fall within the scope of this invention. In this invention, the numerical range "a~b" represents a shortened representation of any combination of real numbers between a and b, where a and b are both real numbers. For example, the numerical range "0~5" means that all real numbers between 0 and 5 have been fully listed in this document, and "0~5" is only a shortened representation of this set of numerical combinations. When a parameter is expressed as an integer ≥2, it is equivalent to listing positive integers that meet the requirements, such as 2, 3, 4, 5, 6, 7, 8, 9, 10, etc. When a parameter is expressed as an integer selected from "2~10", it is equivalent to listing any integer among 2, 3, 4, 5, 6, 7, 8, 9, and 10.
[0045] In this invention, "a combination of at least two" refers to a quantity greater than or equal to 2 unless otherwise specified. For example, "any one or a combination of at least two" means that any one of the listed items can be selected, or a combination of at least two of the listed items formed in a manner that does not conflict and enables the implementation of this invention. In this invention, unless otherwise specified, the features or solutions corresponding to "and / or" cover any one of two or more related listed items, as well as any and all combinations of the related listed items. The arbitrary and all combinations include any two related listed items, any more related listed items, or a combination of all related listed items. For example, "A and / or B" means a set consisting of A, B, and combinations of A and B, where "containing A and / or B" can be understood, depending on the context of the statement, as containing A, containing B, or simultaneously containing both A and B.
[0046] All embodiments and optional embodiments of the present invention, unless otherwise specified and without technical conflict, can be combined to form new technical solutions, and such combinations fall within the scope of the present invention. The term "embodiment" as used in the present invention means that a specific feature, structure, or characteristic described in conjunction with an embodiment can be included in at least one embodiment or implementation of the present invention. The appearance of this phrase in various positions in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment mutually exclusive with other embodiments. Those skilled in the art can explicitly and implicitly understand that the embodiments described in the present invention can be combined with other embodiments without technical conflict. The ordinal numbers "first," "second," "third," and "fourth" used in the present invention, such as "first aspect," "second aspect," "third aspect," and "fourth aspect," are for descriptive purposes only and should not be construed as indicating or implying relative importance or quantity, nor should they be construed as implicitly indicating the importance or quantity of the indicated technical features. They serve only as a non-exhaustive enumeration and do not constitute a closed limitation on quantity.
[0047] The technical solution of the present invention will be further described below with reference to the accompanying drawings and specific embodiments.
[0048] The clarifying agent decomposes or volatilizes at high temperatures, generating a large amount of gas that dissolves in the molten glass during the clarification stage. This supersaturates the glass, increasing its partial pressure and facilitating the penetration of this gas into the bubbles. It also reduces the partial pressure of the existing gas within the bubbles, thus enhancing their ability to absorb other gases from the molten glass. Because the gas from the clarifying agent and the existing gas in the molten glass enter the bubbles together, the bubble diameter increases, accelerating the bubble's escape rate. As these bubbles rise, they also carry some smaller bubbles along with them, acting like mechanical stirring to achieve a highly efficient clarification effect.
[0049] However, currently, photovoltaic glass mainly uses sodium sulfate as a clarifying agent. The complete decomposition temperature of sodium sulfate is about 1400~1450℃. Now, the melting temperature of large-tonnage furnaces can reach 1550~1580℃. A large part of the sodium sulfate is oxidized and decomposed in the melting zone, so by the time it reaches the clarifying zone, sodium sulfate cannot play a sufficient clarifying role.
[0050] Therefore, in one specific embodiment, the present invention provides a composite clarifying agent with the general formula A2B2(SO4)3; wherein A includes Na and K, and B includes Mg, Ca, Sr, Ba and Zn.
[0051] In this invention, the A-site is designed with high entropy, and its alkali metal site is Na. + With K +This allows for the adjustment of lattice size and the introduction of micro-strain. In A₂B₂(SO₄)₃, A represents a combination of Na and K, where Na⁺ has a smaller ionic radius and K⁺ a larger ionic radius. The mixing of these two can optimize lattice energy and ion mobility. By adjusting the sodium-potassium ratio, the orderliness of a single alkali metal is broken, increasing the degree of disorder. The high-entropy design at the B site includes alkaline earth / transition metal sites with Mg. 2+ Ca 2+ 、Sr 2+ Ba 2+ As the main battleground for the high-entropy effect, ions with different radii can be randomly distributed in the crystal lattice, resulting in huge lattice distortion. Zn in B can promote lattice distortion, and because Zn has an atomic number of 30 and a moderate ionic radius, it can further improve the stability after lattice distortion.
[0052] In some embodiments, the general formula of the composite clarifying agent is: (Na x1 K x2 )2(Mg y1 Ca y2 Sr y3 Ba y4 Zn y5 The formula is y1 + y2 + y3 + y4 + y5 = 1. This invention highly mixes seven elements to form an extremely high configurational entropy, stabilizing the crystal structure and achieving a high decomposition point. Simultaneously, the intercalation of elements with different atomic sizes leads to severe lattice distortion, hindering dislocation movement and atomic diffusion, greatly enhancing the overall thermal stability of the crystal and significantly improving decomposition conditions, thus achieving a synergistic effect of multiple superior properties. Furthermore, the lattice distortion and complex chemical environment act like a knot in the crystal, making atomic movement exceptionally difficult, achieving a retarded diffusion effect, thereby widening the thermal reaction range and achieving a performance effect of 1+1>2.
[0053] As one implementation, x1 satisfies: 0.4≤x1≤0.6, for example, it can be 0.4, 0.42, 0.43, 0.45, 0.46, 0.48, 0.5, 0.53, 0.55, 0.56 or 0.6, but is not limited to the listed values. Other unlisted values within this range are also applicable.
[0054] In one implementation, y1 satisfies: 0.1≤y1≤0.4, for example, it can be 0.1, 0.12, 0.13, 0.15, 0.16, 0.18, 0.2, 0.23, 0.25, 0.26, 0.3, 0.32, 0.35, 0.36, 0.38 or 0.4, but is not limited to the listed values. Other unlisted values within this range are also applicable.
[0055] In one implementation, y2 satisfies: 0.1≤y2≤0.4, for example, it can be 0.1, 0.12, 0.13, 0.15, 0.16, 0.18, 0.2, 0.23, 0.25, 0.26, 0.3, 0.32, 0.35, 0.36, 0.38 or 0.4, but is not limited to the listed values. Other unlisted values within this range are also applicable.
[0056] As one implementation, y3 satisfies: 0.1≤y3≤0.3, for example, it can be 0.1, 0.12, 0.13, 0.15, 0.16, 0.18, 0.2, 0.23, 0.25, 0.26, 0.28 or 0.3, but is not limited to the listed values, other unlisted values within this range are also applicable.
[0057] As one implementation, y4 satisfies: 0.1≤y4≤0.3, for example, it can be 0.1, 0.12, 0.13, 0.15, 0.16, 0.18, 0.2, 0.23, 0.25, 0.26, 0.28 or 0.3, but is not limited to the listed values, other unlisted values within this range are also applicable.
[0058] As one implementation, y5 satisfies: 0.1≤y5≤0.2, for example, it can be 0.1, 0.13, 0.15, 0.16, 0.18 or 0.2, but is not limited to the listed values. Other unlisted values within this range are also applicable.
[0059] In another specific embodiment, the present invention provides a method for preparing the composite clarifying agent described in the specific embodiment. The preparation method includes: mixing at least seven kinds of sulfates, adding a dispersing solvent and stirring evenly, and grinding to obtain a mixture, followed by pre-reaction, phase formation treatment and densification treatment in sequence to obtain the composite clarifying agent.
[0060] The at least seven sulfates include at least two primary sulfates and five secondary sulfates.
[0061] Specifically, the two primary sulfates include sodium sulfate and potassium sulfate. The five secondary sulfates include at least magnesium sulfate, calcium sulfate, strontium sulfate, barium sulfate, and zinc sulfate.
[0062] The property parameters of each sulfate in this invention are shown in Table 1: Table 1 shows the different property parameters of each sulfate. In some embodiments, the preparation method specifically includes the following steps: Step (1): Ingredient preparation and wet mixing. Calculate the molar amount of each sulfate according to the target chemical formula, use a combination of water and alcohol as the dispersion medium, and add a dispersant and stir until homogeneous. The alcohol in the dispersion medium includes at least one of methanol, ethanol, or propanol. The dispersion medium is preferably a combination of water and methanol, or a combination of water and propanol, with a preferred mass ratio of 7:3. The dispersant includes any one or a combination of at least two of ammonium polyacrylate, sodium polyacrylate, and polyacrylic acid. Typical but non-limiting combinations include: a combination of ammonium polyacrylate and sodium polyacrylate, a combination of sodium polyacrylate and polyacrylic acid, a combination of ammonium polyacrylate, sodium polyacrylate, and polyacrylic acid, or a combination of ammonium polyacrylate and polyacrylic acid.
[0063] Step (2): Grinding. Place the well-stirred material into a grinding equipment and grind it at a speed of 300-800 rpm for 1-4 hours to obtain a mixture. The grinding equipment includes, but is not limited to, planetary ball mills and vibratory mills.
[0064] The speed can be 300rpm, 350rpm, 400rpm, 450rpm, 500rpm, 550rpm, 600rpm, 650rpm, 700rpm, 750rpm or 800rpm, but is not limited to the listed values. Other unlisted values within this range are also applicable.
[0065] The grinding time is 1 to 4 hours, for example, it can be 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, 3.5 hours or 4 hours, but it is not limited to the listed values. Other unlisted values within this range are also applicable.
[0066] Step (3): Pre-reaction. The mixture from step (2) is placed in an oven and dried for 10-15 hours at 110-120°C. Then it is placed in a muffle furnace and dried for 2-5 hours at 430-470°C. Finally, it is cooled in the furnace to bring the temperature of the mixture to room temperature.
[0067] The temperature of the first drying process is 110~120℃, for example, it can be 110℃, 111℃, 112℃, 113℃, 114℃, 115℃, 116℃, 117℃, 118℃, 119℃ or 120℃, but it is not limited to the listed values. Other unlisted values within this range are also applicable.
[0068] The drying time for one drying process is 10 to 15 hours, for example, 10 hours, 11 hours, 12 hours, 13 hours, 14 hours or 15 hours, but it is not limited to the listed values. Other unlisted values within this range are also applicable.
[0069] The temperature for the secondary drying process is 430~470℃, for example, it can be 430℃, 435℃, 440℃, 445℃, 450℃, 455℃, 460℃, 465℃ or 470℃, but it is not limited to the listed values. Other unlisted values within this range are also applicable.
[0070] The secondary drying process takes 2 to 5 hours, for example, 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, 4.5 hours or 5 hours, but is not limited to the listed values. Other unlisted values within this range are also applicable.
[0071] Step (4): Phase formation treatment. The mixture after the first cooling in step (3) is fed into a muffle furnace and heated to 700~800℃ and held for 1~3h; then heated to 800~850℃ and held for 2~4h; finally cooled in the furnace to complete the second cooling, so that the temperature of the mixture reaches room temperature.
[0072] The temperature after the first heating can be 700℃, 710℃, 720℃, 730℃, 740℃, 750℃, 760℃, 770℃, 780℃, 790℃ or 800℃, but is not limited to the listed values. Other unlisted values within this range are also applicable.
[0073] The holding time after the first heating is 1 to 3 hours, for example, it can be 1 hour, 1.5 hours, 2 hours, 2.5 hours or 3 hours, but it is not limited to the listed values. Other unlisted values within this range are also applicable.
[0074] The temperature after the second heating can be 800℃, 805℃, 810℃, 815℃, 820℃, 825℃, 830℃, 835℃, 840℃, 845℃ or 850℃, but is not limited to the listed values. Other unlisted values within this range are also applicable.
[0075] The holding time after the second heating is 2 to 4 hours, for example, it can be 2 hours, 2.5 hours, 3 hours, 3.5 hours or 4 hours, but it is not limited to the listed values. Other unlisted values within this range are also applicable.
[0076] Furthermore, after the phase formation process is completed, the main phase of the sample is verified using XRD testing.
[0077] Step (5): Densification treatment. The mixture after phase formation treatment in step (4) is ground into powder, and large particles are removed by sieving to obtain a powder mixture with an average particle size of <200 mesh; the powder mixture is then mixed with a binder and granulated to obtain a spherical dense material with a diameter of 0.5~2 mm; the dense material is then sintered at a temperature of 900~1000℃ for 1.5~3 h; finally, it is cooled three times in the furnace to reach room temperature to obtain a composite clarifying agent, which is then stored in a desiccator. The binder includes at least one of polyvinyl alcohol, polyethylene glycol, and polyvinyl butyral, with an addition amount of 3~5 wt%. The granulation is carried out using a spray shaking granulation process.
[0078] The diameter of the spherical dense material can be 0.5mm, 0.6mm, 0.8mm, 1mm, 1.2mm, 1.4mm, 1.5mm, 1.8mm, 1.9mm or 2mm, but is not limited to the listed values. Other unlisted values within this range are also applicable.
[0079] The sintering temperature can be 900℃, 910℃, 920℃, 930℃, 940℃, 950℃, 960℃, 970℃, 980℃, 990℃ or 1000℃, but is not limited to the listed values. Other unlisted values within this range are also applicable.
[0080] The sintering time can be 1.5h, 1.6h, 1.8h, 2h, 2.3h, 2.5h, 2.6h, 2.8h or 3h, but is not limited to the listed values. Other unlisted values within this range are also applicable.
[0081] The amount of adhesive added can be 3wt%, 3.5wt%, 4wt%, 4.5wt%, or 5wt%, but is not limited to the listed values. Other unlisted values within this range are also applicable.
[0082] Furthermore, DSC-TGA was used to confirm whether the composite clarifying agent experienced any weight loss under conditions of 300~900°C.
[0083] In another specific embodiment, the present invention provides an application of the composite clarifying agent described in one specific embodiment, wherein the composite clarifying agent is used for clarifying photovoltaic glass.
[0084] Example 1 This embodiment provides a composite clarifying agent A0, whose general formula is: (Na 0.5 K 0.5 )2(Mg 0.2 Ca 0.2 Sr 0.2Ba 0.2 Zn 0.2 )2(SO4)3; The preparation method of this embodiment includes the following steps: (1) Ingredient preparation and wet mixing. The molar amounts and dosages of each sulfate were calculated according to the target chemical formula, as shown in Tables 2 and 3. Water and ethanol (mass ratio of 7:3) were used as the dispersion medium, and 1 wt% ammonium polyacrylate was added and stirred for 10 min to mix evenly. The amount of dispersion medium added was 40% of the sample weight. (2) Grinding treatment. The well-stirred material is placed in an XZM-100 vibrating mill and ground at a speed of 710 pm for 2 hours to obtain a mixture. (3) Pre-reaction. The mixture from step (2) is placed in an oven and dried for 12 hours at 110±5℃. Then it is placed in a muffle furnace and dried for 4 hours at 450℃ to remove water of crystallization. Finally, it is cooled once in the furnace to bring the temperature of the mixture to room temperature. (4) Phase formation treatment. The mixture after the first cooling in step (3) is fed into a muffle furnace and heated to 720°C and held for 2 hours; then heated to 820°C and held for 3 hours; finally cooled to room temperature. After the phase formation treatment is completed, the main phase of the sample is verified by XRD test. (5) Densification treatment. Grind the mixture after phase formation treatment in step (4) into powder and use a sieve to remove large particles to obtain a powder mixture with an average particle size of <200 mesh; add 3~5wt% of polyvinyl alcohol organic binder (PVA 5% solution) to the powder mixture and mix, then spray shake granulation to obtain spherical dense material with a diameter of 0.5~2mm; then sinter the dense material at a temperature of 950℃ for 2h; finally, cool it three times in the furnace to bring the temperature to room temperature to obtain a composite clarifying agent, which is then stored in a desiccator.
[0085] Example 2 This embodiment provides a composite clarifying agent A2, whose general formula is: (Na 0.6 K 0.4 )2(Mg 0.2 Ca 0.2 Sr 0.2 Ba 0.2 Zn 0.2 )2(SO4)3; In this embodiment, the molar amounts and dosages of each sulfate were calculated according to the target chemical formula, as shown in Tables 2 and 3. The remaining preparation steps, process parameters, and materials were the same as in Example 1.
[0086] The results of XRD testing of the main phase of the sample in this embodiment are as follows: Figure 2 As shown, it is easy to see that the mixture exhibited lattice distortion after two heating cycles.
[0087] Example 3 This embodiment provides a composite clarifying agent A3, whose general formula is: (Na 0.5 K 0.5 )2(Mg 0.15 Ca 0.2 Sr 0.2 Ba 0.25 Zn 0.2 )2(SO4)3; In this embodiment, the molar amounts and dosages of each sulfate were calculated according to the target chemical formula, as shown in Tables 2 and 3. The remaining preparation steps, process parameters, and materials were the same as in Example 1.
[0088] Example 4 This embodiment provides a composite clarifying agent A4, whose general formula is: (Na 0.6 K 0.4 )2(Mg 0.15 Ca 0.2 Sr 0.2 Ba 0.25 Zn 0.2 )2(SO4)3; In this embodiment, the molar amounts and dosages of each sulfate were calculated according to the target chemical formula, as shown in Tables 2 and 3. The remaining preparation steps, process parameters, and materials were the same as in Example 1.
[0089] Comparative Example 1 This comparative example provides a composite clarifying agent A1, whose general formula is: (Na 0.5 K 0.5 )2(Mg 0.25 Ca 0.25 Sr 0.25 Ba 0.25 )2(SO4)3; The molar amounts and dosages of each sulfate were calculated according to the target chemical formula in this comparative example, as shown in Tables 2 and 3. The remaining preparation steps, process parameters, materials, etc. are the same as in Example 1.
[0090] The results of this comparative example, verified by XRD testing of the main phase of the sample, are as follows: Figure 1 As shown, it is easy to see that the mixture exhibited lattice distortion after two heating cycles.
[0091] Table 2 shows the molar amounts of each sulfate in the composite clarifying agent. Table 3 shows the dosage of each sulfate in the composite clarifying agent. like Figure 3 As shown, in this invention, DSC-TGA was used to confirm whether the composite clarifying agent of Examples 1-4 and Comparative Example 1 experienced weight loss at 300-900°C. The sample of Comparative Example 1 showed weight loss in the 800-900°C range, while the samples of Examples 1-4 remained essentially stable upon reheating to 900°C. Additionally, when Na in the A-site ion... + With K + When the molar ratio of alkali metals is 0.6:0.4, the disorder of alkali metals in the crystal reaches its maximum, which makes the dispersion of B-site ions in the crystal lattice better, thereby producing huge lattice distortion and improving the clarification effect.
[0092] Example 5 This embodiment provides a clarifying agent whose materials and formulation are the same as those in Example 1, but the preparation method is different; In this embodiment, the molar amounts and dosages of each sulfate are calculated according to the target chemical formula. Sodium sulfate, potassium sulfate, magnesium sulfate, calcium sulfate, strontium sulfate, barium sulfate and zinc sulfate are directly mixed and sintered, without going through grinding, pre-reaction, phase formation, densification granulation and other processes.
[0093] Comparative Example 2 This comparative example provides a composite clarifying agent with the general formula: (Na 0.6 K 0.4 )2(Mg 0.3 Ba 0.2 Zn 0.5 )2(SO4)3; The molar amounts of each sulfate were calculated according to the target chemical formula in this comparative example, as shown in Table 4. The remaining preparation steps, process parameters, and materials were the same as in Example 1.
[0094] Comparative Example 3 provides a composite clarifying agent with the general formula: (Na 0.6 K 0.4 )2(Ca 0.3 Ba 0.2 Sr 0.5 )2(SO4)3; The molar amounts of each sulfate were calculated according to the target chemical formula in this comparative example, as shown in Table 4. The remaining preparation steps, process parameters, and materials were the same as in Example 1.
[0095] Comparative Example 4 This comparative example provides a composite clarifying agent with the general formula: K2(Mg 0.2 Ca 0.2 Sr 0.2 Ba 0.2 Zn 0.2 )2(SO4)3; The molar amounts of each sulfate were calculated according to the target chemical formula in this comparative example, as shown in Table 4. The remaining preparation steps, process parameters, and materials were the same as in Example 1.
[0096] Comparative Example 5 This comparative example provides a composite clarifying agent with the general formula: (Na 0.6 K 0.4 )2Ba2(SO4)3; The molar amounts of each sulfate were calculated according to the target chemical formula in this comparative example, as shown in Table 4. The remaining preparation steps, process parameters, and materials were the same as in Example 1.
[0097] Comparative Example 6 This comparative example provides a composite clarifying agent with the general formula: (Na 0.5 K 0.5 )2Zn2(SO4)3; The molar amounts of each sulfate were calculated according to the target chemical formula in this comparative example, as shown in Table 4. The remaining preparation steps, process parameters, and materials were the same as in Example 1.
[0098] Comparative Example 7 This comparative example provides a composite clarifying agent with the general formula: (Na 0.5 K 0.5 )2(Sr 0.5 Ca 0.5 )2(SO4)3; The molar amounts of each sulfate were calculated according to the target chemical formula in this comparative example, as shown in Table 4. The remaining preparation steps, process parameters, and materials were the same as in Example 1.
[0099] Comparative Example 8 This comparative example provides a composite clarifying agent with the general formula: (Na 0.5 K 0.5 )2(Ba 0.5 Zn 0.5 )2(SO4)3; The molar amounts of each sulfate were calculated according to the target chemical formula during the comparative preparation of this invention, as shown in Table 4. The remaining preparation steps, process parameters, and materials were the same as in Example 1.
[0100] Table 4 shows the molar amounts of each sulfate in the clarifying agent. In Example 5, the preparation of the clarifying agent involved simply mixing and sintering seven sulfates without grinding, pre-reaction, phase formation, and densification granulation. This resulted in the inability to form lattice distortion, thus failing to meet the requirements for high-temperature clarification. In contrast, Example 1 first used a pre-reaction to remove deionized water and water of crystallization from the sulfates, then achieved lattice distortion through phase formation treatment, and broadened the thermal reaction range of the composite clarifying agent through densification treatment. The resulting composite clarifying agent exhibited superior high-temperature stability.
[0101] Compared to Examples 1-5, the composite clarifying agents in Comparative Examples 2-8 have only one, two, or three metal ions at their B sites, resulting in reduced configurational disorder and decreased crystal structure stability. The alkali metal sites are Na. + With K + Although mixing the two can increase the lattice disorder, their smaller ionic radii and poor crystal structure stability result in a much lower effect on increasing the final decomposition temperature compared to Examples 1-5, leading to unsatisfactory clarification. In contrast, the composite clarifying agent in Comparative Example 4 uses a single K ion at site A, resulting in an ordered distribution of alkali metals in the lattice structure. This leads to lower lattice energy and ion mobility compared to the clarifying agent in Example 1, which uses a combination of Na and K. Furthermore, the high-entropy effect requires at least five main elements to form a multi-element disordered solid solution with each element having an atomic fraction of 5%–35%. By selecting different elements and adjusting the proportions of each component, the crystal structure and phase composition can be altered, thereby achieving a significant performance improvement. However, the number and ratio of high-entropy metal elements at site B in Comparative Examples 1-8 fail to form a stable mixed configuration entropy.
[0102] Comparative Example 9 This comparative example provides a Glauber's salt clarifying agent.
[0103] The reactions of the composite clarifying agent provided in Example 2 of this invention with Glauber's salt in Comparative Example 9 at different temperatures are shown in Table 5.
[0104] Table 5 compares the reaction of the composite clarifying agent in Example 2 with that of Glauber's salt in Comparative Example 9 at different temperatures. The specific reaction process of Example 2 in this invention is as follows: (1) Low temperature stage (<900℃) The samples are dense microspheres ranging from 0.5 to 2 mm in size, and show virtually no reaction during the reaction. A high-entropy stabilization effect dominates; the large lattice distortion energy caused by the multiple elements firmly immobilizes the sulfate ions, preventing their decomposition. The samples exhibit significant inertness. (2) High temperature triggering stage (1150~1300℃) As the temperature rises, the thermal energy is sufficient to overcome the energy barrier brought about by high-entropy stabilization. At this point, the inhomogeneities within the high-entropy structure become reaction points, and lattice thermal vibrations intensify. Due to the differences in the radii and bond energies of the elements within the high-entropy structure, a large amount of localized strain and micro-stress are generated. These micro-regions become areas for sulfate decomposition. At this point, sulfate begins to slowly and continuously decompose on its surface or at grain boundaries, releasing SO3 gas and oxygen. (3) Large-scale decomposition stage (above 1400℃) As the temperature exceeds 1400℃, sulfate ions begin to decompose in stages, resulting in a delayed and long-lasting clarification effect.
[0105] In addition, the present invention uses the composite clarifying agent provided in Example 2 and the sodium sulfate clarifying agent provided in Comparative Example 9 to conduct high-temperature visual melting experiments to verify and compare the similarities and differences in high-temperature visual melting within the same time period, thereby confirming the high-temperature clarification phenomenon and clarification effect. The specific method includes: weighing approximately 35g of photovoltaic glass batch material (clarifying agent content 2.8wt%) and heating it in the furnace. Specifically, the heating rate is 10℃ / min when heating from room temperature to 1200℃, and 5℃ / min when heating from 1200℃ to 1550℃. The temperature is then held at 1550℃ for 1 hour. Results... Figure 4 and Figure 5 As shown. Figure 4 The melting test results of the composite clarifying agent provided in Example 2 are as follows. Figure 5 The melting test results of the Glauber's salt clarifying agent provided in Comparative Example 9.
[0106] Depend on Figure 4 and Figure 5 It can be seen that when using Glauber's salt as a clarifying agent in Comparative Example 9, a large number of bubbles began to appear at 1400℃, and the clarifying agent was almost completely consumed when the temperature rose to 1550℃. In contrast, the composite clarifying agent in Example 2 only began to produce a large number of bubbles at 1500℃, and when the temperature rose to 1550℃, a large number of large bubbles appeared, achieving a clarifying effect. Further comparison using high-temperature visual images shows that the composite clarifying agent in Example 2 has a higher decomposition temperature and a better clarifying effect.
[0107] In summary, compared with traditional clarifying agents, the composite clarifying agent of the present invention can remain stable at low temperatures, reduce low-temperature decomposition, and achieve continuous and controllable decomposition in the high-temperature zone, thus extending the clarification time and temperature range, making it more suitable for the clarification of large-size photovoltaic melting furnace glass.
[0108] Comparative Example 10 This comparative example provides a clarifying agent consisting of a single K2SO4.
[0109] Comparative Example 11 This comparative example provides a clarifying agent consisting of a single CaSO4.
[0110] Comparative Example 12 This comparative example provides a clarifying agent consisting of a single BaSO4.
[0111] Comparative Example 13 This comparative example provides a clarifying agent consisting of a single ZnSO4.
[0112] Comparative Example 14 This comparative example provides a clarifying agent consisting of a single MgSO4.
[0113] Comparative Example 15 This comparative example provides a clarifying agent consisting of a single SrSO4.
[0114] Compared to Example 1, Comparative Examples 10-15 all used a single sulfate as a clarifying agent, and its clarifying effect on the glass melt was significantly reduced. This is because the decomposition temperature of a single sulfate is low, which cannot meet the temperature curve of photovoltaic glass melting-clarification-cooling. During the glass melting process, some of the clarifying agent undergoes oxidative decomposition, and as the clarification process proceeds, the clarification effect of the sulfate gradually decreases or even becomes ineffective.
[0115] The composite clarifying agent of this invention employs a hybrid design of high entropy at both the A-site and B-site, resulting in a higher decomposition temperature. It remains stable at low temperatures while exhibiting delayed and controllable gas release within a specific high-temperature window, achieving a high-temperature clarification effect that is more ideal than traditional clarifying agents. Furthermore, the composite clarifying agent of this invention has an optimal ratio, and through multi-stage decomposition of composite minerals, it achieves a wider thermal reaction range, maximizing the clarification effect and meeting the clarification requirements of large-scale photovoltaic glass furnaces. In addition, the presence of multiple elements within a single crystal lattice in the composite clarifying agent generates a large configurational entropy. This entropy effect significantly stabilizes the crystal structure and inhibits the precipitation of other competing phases.
[0116] The preferred embodiments of the present invention have been described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the scope of the technical concept of the present invention, various simple modifications can be made to the technical solution of the present invention, and these simple modifications all fall within the protection scope of the present invention.
[0117] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not describe the various possible combinations separately.
[0118] Furthermore, various different embodiments of the present invention can be combined in any way, as long as they do not violate the spirit of the present invention, they should also be regarded as the content disclosed by the present invention.
Claims
1. A composite clarifying agent, characterized in that, The general formula of the composite clarifying agent is: (Na x1 K x2 )2(Mg y1 Ca y2 Sr y3 Ba y4 Zn y5 )2(SO4)3; Where x1+x2=1, y1+y2+y3+y4+y5=1; The x1 satisfies: 0.4 ≤ x1 ≤ 0.6; The condition y1 satisfies: 0.1 ≤ y1 ≤ 0.4; The condition y2 satisfies: 0.1 ≤ y2 ≤ 0.4; The condition y3 satisfies: 0.1 ≤ y3 ≤ 0.3; The condition y4 satisfies: 0.1 ≤ y4 ≤ 0.3; The condition y5 satisfies: 0.1≤y5≤0.
2.
2. A method for preparing the composite clarifying agent as described in claim 1, characterized in that, The preparation method includes: At least seven sulfates are mixed and then a dispersing solvent is added and stirred until homogeneous. The mixture is then ground to obtain a mixture, which is then subjected to pre-reaction, phase formation treatment and densification treatment in sequence to obtain a composite clarifying agent.
3. The preparation method according to claim 2, characterized in that, The at least seven sulfates include at least two primary sulfates and five secondary sulfates; The two primary sulfates include sodium sulfate and potassium sulfate; The five second sulfates include at least magnesium sulfate, calcium sulfate, strontium sulfate, barium sulfate, and zinc sulfate; The dispersion medium used in the mixing process includes water and alcohols, wherein the alcohols include at least one of methanol, ethanol or propanol; The dispersant used in the mixing process includes at least one of ammonium polyacrylate, sodium polyacrylate, and polyacrylic acid; The grinding process is performed at a speed of 300-800 rpm for 1-4 hours.
4. The preparation method according to claim 2, characterized in that, The pre-reaction includes a first drying process, a second drying process, and a first cooling process performed sequentially. The temperature of the first drying process is 110~120℃, and the time is 10~15h; The secondary drying process is carried out at a temperature of 430~470℃ for 2~5 hours. The primary cooling includes: cooling the furnace to room temperature.
5. The preparation method according to claim 2, characterized in that, The phase formation process includes: sequentially heating the pre-reaction mixture once, heating it a second time, and cooling it a second time. The temperature after the first heating is 700~800℃, and the holding time is 1~3h; The temperature after the second heating is 800~850℃, and the holding time is 2~4h; The secondary cooling includes: cooling the furnace to room temperature.
6. The preparation method according to claim 2, characterized in that, The densification process includes: The mixture after phase formation treatment is pulverized to obtain a powder mixture; The powder mixture is then mixed with a binder and granulated to obtain a dense material. The dense material is subjected to sintering and cooling three times in sequence to obtain the composite clarifying agent; The average particle size of the powder mixture is <200 mesh; The diameter of the dense material is 0.5~2mm; The sintering process is carried out at a temperature of 900~950℃ for 1.5~3 hours. The three cooling processes include: cooling to room temperature with the furnace, and then storing in a desiccator.
7. An application of the composite clarifying agent as described in claim 1, characterized in that, The composite clarifying agent is used for clarifying photovoltaic glass.
Citation Information
Patent Citations
Method for producing clear glass or clear drawn glass by utilizing special refining process
CN102363553A
Composite clarifying agent containing strontium carbonate
CN120864789A